Giant ovarian serous cystadenoma. A case report - Jorge Luis Estepa Pérez; Tahiluma Santana Pedrasa; Daniel Olivera Fajardo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Ovarian tumors are not as common as uterus and breast tumors. They are regarded as the third group of women benign and malignant tumors. Ovarian serous cystadenomas arise from the superficial coelomic epithelium and are composed of cystic areas. There are macroscopically small tumors and massive tumors occupying the entire pelvis and even the abdominal cavity. The case of a 57 years old female patient with a history of apparent good health that attended consultation because of abdomen enlargement after a year of evolution is presented. The patient referred also nausea, loss of appetite and abdominal left flank pain. She was treated at the General Surgery Department of the General University Hospital "Dr. Gustavo Aldereguía Lima". Left oophorectomy was performed. Histopathological examination showed a giant serous ovarian cystadenoma. Pos-surgery evolution was satisfactory.